2018
DOI: 10.1002/ijc.31971
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive analysis of HPV infection, EGFR exon 20 mutations and LINE1 hypomethylation as risk factors for malignant transformation of sinonasal‐inverted papilloma to squamous cell carcinoma

Abstract: Different risk factors are suspected to be involved in malignant transformation of sinonasal papillomas and include HPV infection, tobacco smoking, occupational exposure, EGFR/KRAS mutations and DNA methylation alterations. In our study, 25 inverted sinonasal papillomas (ISPs), 5 oncocytic sinonasal papillomas (OSP) and 35 squamous cell carcinomas (SCCs) from 54 patients were genotyped for 10 genes involved in EGFR signalling. HPV-DNA detection was performed by in-situ hybridisation and LINE-1 methylation was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

9
56
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(74 citation statements)
references
References 37 publications
9
56
4
Order By: Relevance
“…Our results demonstrated transcriptionally-active high-risk HPV in 23.5% (CI95: 10.7-41.2%) cases of SNSCC. This finding is consistent with results of 7 other studies that found proportions of transcriptionally-active HPV (by mRNA or inference from DNA and p16/ISH) in SNSCCs ranging from 11.4-31.1% [10][11][12][13][14][15][16]. Consequently, our results support the etiological role of high-risk HPV in some squamous cell carcinomas arising in sinonasal tract.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Our results demonstrated transcriptionally-active high-risk HPV in 23.5% (CI95: 10.7-41.2%) cases of SNSCC. This finding is consistent with results of 7 other studies that found proportions of transcriptionally-active HPV (by mRNA or inference from DNA and p16/ISH) in SNSCCs ranging from 11.4-31.1% [10][11][12][13][14][15][16]. Consequently, our results support the etiological role of high-risk HPV in some squamous cell carcinomas arising in sinonasal tract.…”
Section: Discussionsupporting
confidence: 93%
“…Based on the cancer registry data, which do not distinguish between transcriptionally-en CC has been reported as a favorable prognostic factor [17] or a variable not associated with survival [18]. However, only a few studies reported HPV-positivity of sinonasal carcinomas in the context of transcriptionallyactive high-risk HPV [10][11][12][13][14][15][16]. Two of these studies found significantly improved OS and DFS in HPV-positive groups [11,13], and two studies showed a trend towards better prognosis without statistical significance [14,15].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, some studies have Table I. reported that sinonasal IP progression to SCC was significantly associated with the presence of human papillomavirus (HPV) infection (14,15). However, Mohajeri et al compared HPV positivity among sinonasal IP samples and those from patients with SCC by immunohistochemistry and found that HPV was not supported as an etiological driver of IP development or progression to SCC (16).…”
Section: Discussionmentioning
confidence: 99%
“…The precise nature of this oncogenic transformation has not been clearly defined; thus, there is an unmet need for further studies into pathogenetic factors of SP-derived SCCs, including the ambiguous role of human papilloma virus type 16 (HPV-16) infection [5,[7][8][9]. Moreover, further evidence is warranted to support tobacco smoking as an etiological factor, despite it relates with increased risk of sinonasal SCCs and is a well-established, modifiable risk factor for head and neck cancer [10].…”
Section: Discussionmentioning
confidence: 99%